Progress toward New Public Governance in Romania. Issue 3 (12th August 2019) - Stanica, Cristina Maria; Aristigueta, Maria
Abstract : Purpose: New Public Governance is becoming an important framework for managing the public sector in the era of collaborative governance. The purpose of this paper is to explore the extent to which New Public Governance as a framework is limited to the political and administrative context of Romania and to create a connection between good governance and New Public Governance through operationalizing the concepts and clarifying their inter-dependency. New public leadership skills are required from both horizontal and vertical approaches, in order to tackle the country's wicked problems. Design/methodology/approach: Through the use of qualitative methods, such as document analysis of Cooperation and Verification Mechanism reports of the European Commission on Romania, and expert interviews with a focus on governance aspects, the paper seeks to clarify the challenges that Romania faces in terms of democratization given the current political and administrative context. Findings: Findings in Romania reveal little agreement on progress in government effectiveness, regulatory quality and implementation of the rule of law. However, progress has been noted on voice and accountability and strengthening democracy. Research limitations/implications: The authors discuss the uncertainty that the concept of good governance has created from an international organizations' perspective in developing countries, and define the good governance infrastructure as a means of bringing governance closer to the complex and changing context of each country. The paper aims to clarify the connection between good governance and New Public Governance, by assessing contextual factors in developing countries. Practical implications: The practical implications of the study are related to the possibility of this paper to inform other developing countries on the conditions that are necessary in order to adhere to New Public Governance. The paper has implications in proposing the use of the good governance infrastructure as a helpful concept when considering democratic frameworks for research and practice. Social implications: The social implications of this paper are connected to the current political, administrative and social context of the Central and Eastern European region and its component countries. Improving democratic practices, through advancing the importance of good governance indicators in switching to a public governance perspective in public administration, is the main outcome of New Public Governance-style reforms. Originality/value: The paper's originality stands in designing the premises for the "good governance infrastructure" as a new concept that aims to bridge the gap between good governance and New Public Governance, and bring more conceptual clarity. Being supported by evidence, through the use of primary data generated by expert interview analysis, the new concept can improve and encourage further research on this topic.